Effect of red and black ginseng on cholinergic markers, presynaptic markers, and neurotrophins in the brain of aged mice - Lee, Mi Ra (Food Sci Biotechnol, 2017)
This study investigated the effects of chronic administration of red ginseng extract (RGE) and black ginseng extract (BGE) on memory impairment in aged (18-month-old) mice. RGE and BGE (200 mg/kg) were orally administered for 16 weeks. Aging induced DNA damage; however, RGE and BGE protected DNA from damage and allowed for DNA recovery in blood lymphocytes. Choline acetyltransferase, vesicular acetylcholine transporter, growth-associated protein 43, synaptosomal-associated protein 25, nerve growth factor, and brain-derived neurotrophic factor protein expression were significantly increased after treatment with RGE and BGE. These data suggest that chronic administration of red ginseng and black ginseng may decrease the cognitive deficits associated with normal aging.